Water and solute permeability of plant cuticles measurement and data analysis - Schreiber, Lukas. (Springer, 2009)
The study of permeability of plant cuticles is of gaining interest since transport processes play a crucial role in plant ecology, plant stress tolerance, plant growth regulation, plant protection, phytopathology and the accumulation of xenobiotics in plants. Penetration of neutral and ionic solutes can be modeled and predicted, provided suitable experiments based on sound theories are conducted using whole leaves, leaf disks or isolated cuticles. These measurements allow estimating water loss from plants, including transgenic plants with an altered cuticle and wax composition. Based on representative examples, the authors describe the basics of sorption, diffusion and permeability characteristics of cuticles. They present suitable experimental approaches for solving specific problems related to transport of water and solutes across cuticles. Data analysis stresses quantitative structure property relations. Pitfalls and erroneous interpretations of experimental data are shown. Calculations are used to point out physiological and ecological consequences of the equations developed and problems at the end of each chapter provide some additional exercises. Chemistry and Structure of Cuticles as Related to Water and Solute Permeability -- Quantitative Description of Mass Transfer -- Permeance, Diffusion and Partition Coefficients: Units and Their Conversion -- Water Permeability -- Penetration of Ionic Solutes -- Diffusion of Non-Electrolytes -- Accelerators Increase Solute Permeability of Cuticles -- Effects of Temperature on Sorption and Diffusion of Solutes and Penetration of Water -- General Methods, Sources of Errors, and Limitations in Data Analysis.